Open-Air Music in Warsaw Between the World Wars - Dziadek Magdalena (Musicology Today)
The aim of the paper is to situate the most important open-air venues where music was performed on the map of interwar Warsaw. This includes venues in city parks, restaurant tea gardens, streets and squares where mass celebrations and demonstrations took place, as well as the courtyards of tenement houses frequented by street players and singers. In addition to live music, that coming from the radio, gramophone records, as well as megaphones installed in parks and streets has been taken into account. On the basis of press reports, taken mainly from the Kurier Warszawski (Warsaw's largest daily newspaper), as well as works of fiction and diaries, the repertoire of works performed in the open air has been reconstructed. The organisers and performers of concerts, open-air shows, and street marches during which music was performed have also been listed. The material is divided into contexts connected with the everyday life of Warsaw's bourgeoisie and working class (during which music, functioning independently or as part of theatrical, cabaret and film performances, functioned as entertainment) and those belonging to the official-public or ceremonial sphere (celebrations of religious and national holidays, military parades, spontaneous demonstrations of supporters of various political groups). Special emphasis has been placed on recreating the social and political context of the latter type of events, which highlight the role of interwar Warsaw as the capital of the state.